The Potential for Ocean-Based Climate Action: Negative Emissions Technologies and Beyond - Gattuso, Jean-Pierre; Williamson, Phillip; Duarte, Carlos M.; Magnan, Alexandre K. (Frontiers in Climate, 2021)
Four ocean-based negative emissions technologies (NETs) are assessed in comparison to eight other ocean-based measures. Their role in revising UNFCCC Parties’ future Nationally Determined Contributions is discussed in the broad context of ocean-based actions for both mitigation and ecological adaptation. All measures are clustered in three policy-relevant categories (Decisive, Low Regret, Concept Stage). None of the ocean-based NETs assessed are identified as Decisive at this stage. One is Low Regret (Restoring and increasing coastal vegetation), and three are at Concept Stage, one with low to moderate potential disbenefits (Marine bioenergy with carbon capture and storage) and two with potentially high disbenefits (Enhancing open-ocean productivity and Enhancing weathering and alkalinization). Ocean-based NETs are uncertain but potentially highly effective. They have high priority for research and development.